Variability of levels and composition of PM10 and PM2.5 in the Barcelona metro system - E. de Miguel (Atmospheric Chemistry and Physics, 2012)
From an environmental perspective, the underground metro system is one of the cleanest forms of public transportation in urban agglomerations. Current studies report contradicting results regarding air quality in the metro systems: whereas some reveal poor air quality, others report PM levels which are lower or of the same order of magnitude than those measured in traffic sites above ground level. The present work assesses summer and winter indoor air quality and passenger exposure in the Barcelona metro, focusing on PM levels and their metal contents. In addition, the impact on indoor air quality of platform screen door systems (automated systems consisting of closed rail track and platforms) is evaluated, to determine whether these systems reduce passenger exposure to PM when compared with conventional systems (open tracks and platforms). In the Barcelona metro PM levels inside the trains in summer are amongst the lowest reported for worldwide metro systems (11–32 μg m−3 PM2.5). This is most likely due to the air conditioning system working in all carriages of the Barcelona metro during the whole year. Levels were considerably higher on the platforms, reaching mean levels of 46 and 125 μg m3 in the new (L9) and old (L3) lines, respectively. PM10 data are also reported in the present study, but comparison with other metro systems is difficult due to the scarcity of data compared with PM2.5. Results showed distinct PM daily cycles, with a drastic increase from 06:00 to 07:00 a.m., a diurnal maximum from 07:00 to 10:00 p.m., and marked decrease between 10:00 p.m. and 05:00 a.m. The elements with the highest enrichment were those associated with wheel or brake abrasion products (Ba, Fe, Cu, Mn, Cr, Sb, As, Mo, Co, Sr, among others). Laminar hematite (Fe2O3) was the dominant particle type, being mainly originated by mechanical abrasion of the rail track and wheels. Regarding passenger exposure to PM, the contribution of commuting by metro was estimated to account for around 10% of the daily exposure. However, this contribution may be one order of magnitude higher when specific matals are considered. Finally, we conclude that the implementation of platform screen door systems results in reductions of both PM levels and metal concentrations. In addition an advanced optimized ventilation system gave even a much higher efficiency in reducing exposure to PM of metro commuters. Combining these two features PM exposure levels in the platforms may be reduced down by a factor of 7 with respect the old subway lines in Barcelona.